A new HLA‐B*39 allele, B*39:168, closely related to B*39:05:01:02. (20th October 2020) - Planelles, Dolores; Balas, Antonio; Rodríguez‐Cebria, Manuel; Vicario, Jose L.
Abstract : A new HLA‐B*39:168 was characterized in a Caucasian Spanish individual.